Efficacy and safety of golimumab in Indian patients with rheumatoid arthritis: Subgroup data from GO‐MORE study. (26th July 2016) - Pal, Sarvajeet; Veeravalli, Sarath Chandra Mouli; Das, Siddharth Kumar; Shobha, Vineeta; Uppuluri, Ramakrishna Rao; Dharmanand, B G; Nadkar, Milind; Hsia, Elizabeth; Fei, Kaiyin; Yao, Ruji; Khalifa, Ahmed
Abstract: Aim: To conduct a subgroup analysis of GO‐MORE trial Part 1, comparing efficacy and safety of add‐on subcutaneous golimumab therapy in rheumatoid arthritis (RA) patients enrolled from and outside India. Methods: GO‐MORE was an open‐label, multicenter, prospective trial of add‐on golimumab in biologic‐naïve RA patients, having active disease despite being on conventional DMARD regimen(s). Part 1 of the study was chosen as the focus of this subgroup analysis because a substantial number of Indian patients (106) were enrolled compared to no Indian patients in Part 2. The primary efficacy outcome was proportion of patients achieving good to moderate DAS28‐ESR (Disease Activity Score of 28 joints calculated using erythrocyte sedimentation rate) European League Against Rheumatism (EULAR) response at month 6. Results: Efficacy evaluable population comprised of 105 and 3175 patients from India and outside India, respectively. Safety analysis included 106 patients enrolled from India and 3251 from outside India. A higher proportion of Indian patients had a high disease activity as measured by DAS28 ESR than outside India patients. At month 6, the proportion of Indian and non‐Indian patients achieving DAS28‐ESR, DAS28 – C‐reactive protein, simplified disease activity index (SDAI) remission, and EuroQoL Quality‐of‐Life Questionnaire (EQ‐5D) scores were comparable. Incidence of all adverse events was lower in Indian patients. There were no deaths, cases of tuberculosis or malignancy reported in the patients from India at month 6. Conclusions: The efficacy and safety results with add‐on golimumab were consistent between RA patients from India and outside India, despite high baseline disease activity in the Indian patients.